Sleepless Knight - Sturm, James, 1965- (Adventures in cartooning, Jr. book, 2015)
"The Knight can't wait for her first camping trip. She and her horse Edward pack everything they need--including her beloved Teddy--and head out into the woods. But when it's time for bed, Teddy is nowhere to be found"--